Campur Kode dalam Bloger Youtube Agung Hapsah “Gak Bisa Basa Enggress”: Tinjauan Analisis Wacana Kritis - Numertayasa, I Wayan; Ariawan, I Nengah Tegteg (GERAM: Gerakan Aktif Menulis, 2023)
The intention of this research is to uncover the mixing code of YouTube blogger Agung Hapsah. Mixing code is the simultaneous use of two or more languages in a language's speech actions when speakers are speaking. This study employs a qualitative descriptive approach in tandem with Norman Fairclough's theory. The data in this research was analyzed utilizing data collection techniques and the note-taking technique, obtaining 19 mixed-code data points. According to the results of this study, 1) there are 11 data insertions of elemental codes in the form of words; 2) there are 3 data insertions of elemental codes resulting in phrases; and 3) there are 3 data insertions of elemental codes in the form of idioms. 4) There are 3 insertion data elements of repetition of words in leksykal codes. 5) There is one insertion element in the form of clausa. Each data is a mixed code for introducing word elements in two languages, such as English, which are inserted into the Indonesian language structure, and there is one data that comprises a mixed code for inserting regional language aspects into the Indonesian language structure.